The study on attributes of urban plaza and design implications - Liu, Le, 1983-; Mahbob Salim, supervisor; Fakulti Alam Bina (2010)
Thesis (Sarjana Sains (Rekabentuk Bandar)) - Universiti Teknologi Malaysia, 2010